2022
DOI: 10.3390/nano12050729
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Electrochemical Performance of Ni-Rich LiNi0.88Co0.09Al0.03O2 Cathodes through Tungsten-Doping for Lithium-Ion Batteries

Abstract: The tungsten-doped (0.5 and 1.0 mol%) LiNi0.88Co0.09Al0.03O2 (NCA) cathode materials are manufactured to systematically examine the stabilizing effect of W-doping. The 1.0 mol% W-doped LiNi0.88Co0.09Al0.03O2 (W1.0-NCA) cathodes deliver 173.5 mAh g−1 even after 100 cycles at 1 C, which is 95.2% of the initial capacity. While the capacity retention of NCA cathodes cycled in identical conditions is 86.3%. The optimal performances of the W1.0-NCA could be ascribed to the suppression of impendence increase and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…W doping of NCA is known to increase electronic and ionic conductivity, decrease cation mixing, and mitigate particle cracking. 50 The negative electrode consisted of graphite with SiO x particles, which had a coating or interphase layer with a thickness up to 100 nm. The use of SiO x chemistry in the negative electrode has been found to improve its specific capacity and lower degradation compared to pure Si.…”
Section: Resultsmentioning
confidence: 99%
“…W doping of NCA is known to increase electronic and ionic conductivity, decrease cation mixing, and mitigate particle cracking. 50 The negative electrode consisted of graphite with SiO x particles, which had a coating or interphase layer with a thickness up to 100 nm. The use of SiO x chemistry in the negative electrode has been found to improve its specific capacity and lower degradation compared to pure Si.…”
Section: Resultsmentioning
confidence: 99%
“…21 These characteristics translate to an observed reduction in degradation and improvements to lithium diffusion kinetics when Nb 5+ is employed as a dopant. Other element dopants with comparable ionic radius and higher valence than the TMs in LTMOs, such as V 5+ , 22–24 Ta 5+ , 25–27 Mo 6+ , 28–30 and W 6+ , 31–33 have also been reported to exhibit similar improvements. Another work has outlined the impact of these and various other dopants and coating materials on Ni-rich CAMs.…”
Section: Introductionmentioning
confidence: 92%
“…147 Various cations, such as Na + , K + , Mg 2+ , Al 3+ , Nb 5+ , V + , W 6+ , Mo 6+ , Zr 4+ , Si 4+ , etc., are successfully doped into the crystal moiety of high Ni-NCMs/NCAs to improve the structural stability, conductivity and electrochemical performance. [148][149][150][151][152][153][154] Shen et al have doped Ni 0.6 Co 0.05 Mn 0.35 O 2 with varying amounts of Na + and K + (1-3%) and evaluated the electrochemical performance. 36 It was observed that 2% Na + and 1% K + doping could efficiently improve the performance individually.…”
Section: Cation/anion Dopingmentioning
confidence: 99%